PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THE POWER OF TWO UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS KELAS IV SDN 164 PEKANBARU - Siska Idola; Lazim N; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The background of the problems in this research was the low students learning achievement at fourth grade of SDN 164 Pekanbaru with an average value of 65.8 which was under the KKM set school is 75. This research was aimed to improve students learning achievement in social subject at four grade of SDN 164 Pekanbaru with the implementation of cooperative learning model type The Power of Two. This research was a classroom action research (PTK). The research subject was the fourth grade students of SDN 164 Pekanbaru numbering as many as 42 students consisting of 26 male, 16 female. Data were collected by observation techniques and engineering achievement test. The result of research concluded that the implementation of cooperative learning model type The Power of Two can improve students learning achievement in social subjects at fourth grade of SDN 164 Pekanbaru.Keywords: The Power of Two, Learning Achievement